Selecting Aptamers for a Glycoprotein through the Incorporation of the Boronic Acid Moiety - Minyong Li; Na Lin; Zhen Huang; Lüpei Du; Craig Altier; Hao Fang; Binghe Wang (2008)
The first general method for the selection of boronic acid−based aptamers (boronolectins) that allows for glycan substructure focusing is described. Using fibrinogen as a model glycoprotein, we have selected boronic acid-modified DNA aptamers that have high affinities (low nM Kd) and the ability to recognize changes in the glycosylation site. The method developed should also be applicable to the development of aptamers for other glycoproducts, such as glycolipids and glycopeptides.